Current therapeutic strategies of anti-HER2 treatment in advanced breast cancer patients - Huszno, Joanna; Nowara, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2016)
The HER2/neu ( ERBB2 ) oncogene is amplified and/or overexpressed in approximately 20% of breast cancers, and is a strong prognostic factor for relapse and poor overall survival, particularly in node-positive patients. It is also an important predictor for response to trastuzumab, which has established efficacy against breast cancer with overexpression or amplification of the HER2 oncogene. Treatment with the anti-HER2 humanized monoclonal antibody – trastuzumab significantly improves progression-free and overall survival among patients with HER2-positive breast cancer. However, in most patients with HER2-positive metastatic breast cancer, the disease progresses occurred, what cause the need for new targeted therapies for advanced disease. In clinical trials, there are tested new drugs to improve the results of treatment for this group of patients. This paper presents new drugs introduced into clinical practice for treatment of advanced breast cancer, whose molecular target are receptors of the HER2 family. In addition, new therapeutic strategies and drugs that are currently in clinical researches are discussed.